Feeding Problems at Different Level of Gross Motor Function in Children with Cerebral Palsy - Shahbaz Ahmad; Faiza Sharif; Iqra Karamat (Journal Riphah College of Rehabilitation Sciences, 2020)
Objective: To determine the Association and frequency of feeding problems at different level of Gross Motor Function among Cerebral Palsy children.